Planning and Building a Reliable, Secure, and Scalable Corporate Network - Hafi Ilmiyanor, Akhmad; Azmi, Muhammad; Delakamin, Putri Ika; Nisa, Zapiratun (INSTALL: Information System and Technology Journal, 2025)
The development of information and communication technology is driving the increasing need for reliable, secure, and scalable corporate network infrastructure, especially in higher education institutions. Building E of Sari Mulia University as a new facility to support academic and operational activities need network system that is able to provide fast, stable, and secure data connectivity. This research discusses the planning and construction of an integrated corporate network in Building E, Sari Mulia University. The methods used include network needs analysis, network architecture design, infrastructure implementation, system configuration and security, and network testing and documentation. The design results show that the network built is able to provide stable wired and wireless connectivity, support centralized network management, and ensure data security through the implementation of network segmentation, firewalls, and Virtual Private Network (VPN). In addition, the resulting network design is scalable so that it can be developed according to the needs of the university in the future. Thus, the designed corporate network is expected to be able to support academic and operational activities optimally and support the digital transformation of Universitas Sari Mulia in a sustainable manner.